Edukasi dan Praktik Pemanfaatan Tanaman Ki Encok (Plumbago Zeylanica L.) Bagi Ibu Rumah Tangga di Kecamatan Jakabaring Palembang - Purwoko, Mitayani; Hastuti, Riliani; Hartina, Nabila; Sulistiani, Taris Ade; Anzani, Tsabitah Zahra Dwi (Jurnal Pelayanan dan Pengabdian Masyarakat (Pamas), 2025)
Herbal plants can be consumed or applied to the painful joints. One of the Indonesian herbal plants that is useful for relieving joint pain or gout is the Ki Encok plant (Plumbago zeylanica L.). However, there are side effects that can arise if the leaves are applied for a long time, namely causing the skin to turn black and not disappear for up to two weeks. This is also called Irritant Contact Dermatitis. The purpose of this activity is to provide education and practice on how to use Ki Encok leaves to treat joint pain and education on how to use herbal plants that are good for skin health. The output of this community service activity is an increase in participants' knowledge about the benefits of the Ki Encok plant and how to prevent skin disorders due to the use of the Ki Encok plant, as well as an increase in skills in preparing Ki Encok leaf mash and applying it to painful joints. The pre-test results showed an average score of 66.67 and the post-test results showed an average score of 86.67. There was an increase in the score of 20 points. In conclusion, providing health education on the use of herbal plants to treat gout and preventing irritant contact dermatitis due to the use of herbs can increase public knowledge. Keywords: encok leaves, contact dermatitis, joint pain